Gangguan Stres Pascatrauma Dan Panggilan Penginjilan: Sebuah Refleksi Teologis dan Psikologis dari Kitab Yunus - Stimson Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2021)
Evangelism is the Great Commission from God to mankind. God gave the same mandate to Jonah, but Jonah bravely refused the Great call. This study tries to find out why Jonah was